Pentarikhan Jejak Belah Zirkon dan Implikasinya Terhadap Genesa Batuan Granitik Di Daerah Kayutanam, Padang Panjang, Sumatera Barat - Permanadewi, Sam (Jurnal Geologi dan Sumberdaya Mineral, 2018)
The outcrop of granitic rocks at Kayutanam area, Padang Panjang, West Sumatera is known occured during Neogene. The fission track dating method can determine the absolute age of the granitic rock in this area and the intrusive period. Fission track analysis results the age of these granitic rocks is generated from 5.1 ± 0.5 to 19.9 ± 1.5 mys. Considering these dating result comprehend with petrographic analysis and the location of the granitic rocks it is suggested that the granitic intrusion occurred in three periods. The first granitic intrusion period took place in the Upper part of Early Miocene (19.9 mys). The second granitic intrusion period occured during the Lower - Upper part of Middle Miocene (15.0-11.2 mys). While the latest granitic intrusion is determined generated on the Lower part of Late Miocene- Early Pliocene (10.8-5.1 mys).Keyword : Fission track dating, petrography, granitic rocks, West Sumatera, Miocene.